KAJIAN KEMAMPUAN LITERASI KUANTITATIF SISWA SMA 8 KOTA BENGKULU - Yosmar, Siska; Afandi, Nur; Swita, Baki (Jurnal Pengabdi, 2019)
Quantitative literacy is the ability and confidence in using basic mathematical concepts and calculating operations needed for problem solving, decision making of economic problems and their applications in everyday life. Mastery of basic mathematics is an absolute requirement for achieving good quantitative literacy skills. The aim of this activity was to improve mathematical literacy skills of the students at SMA 8 Bengkulu City. The activities were begun by giving pre-tests to students, preparing of modules, presenting the materials of the modules in classroom, practicing through LKS and post-tests. Several techniques, methods and approaches in number counting operations have been presented in this activity. This activity has provided an increase in quantitative literacy skills in class XI IIS-1 SMA 8 Kota Bengkulu. Even so, the improvement of students' abilities can be said to be less optimal because there are still some questions that cannot be answered by almost all students. Therefore, cooperation and involvement of all parties is needed to improve students' quantitative literacy skills and follow-up activities in an effort to strengthen quantitative literacy skills.